Historical Psychology: the Subject and Structure (Experienceof the Scientific Reflection) - А А Korolyov (Peoples' Friendship University of Russia (RUDN University), 2008)
Through the prism of the interdisciplinary approach the author examines a number of the methodological and theoretical matters connected with the definition of the subject, structure and methods of historical psychology as integral branch of social science. In the article the detailed historiographic review of the problem is presented, rather a successful attempt to reveal the contents of the concept «historical psychology» is undertaken, an original view of the problem field and the methodological bases is stated, the categorial apparatus of the arising branch of social science is characterized.